COPD increases cardiac mortality in patients presenting with ventricular tachyarrhythmias and aborted cardiac arrest. (December 2018) - Rusnak, Jonas; Behnes, Michael; Schupp, Tobias; Reiser, Linda; Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Hoppner, Jorge; Weidner, Kathrin; El-Battrawy, Ibrahim; et al.
Abstract: Objectives: The study sought to assess the prognostic impact of COPD in patients presenting with ventricular tachyarrhythmias and sudden cardiac arrest (SCA) on admission. Background: Data regarding the outcome of patients with COPD presenting with ventricular tachyarrhythmias and SCA is limited. Methods: A large retrospective registry was used including all consecutive patients presenting with ventricular tachycardia (VT), fibrillation (VF) and SCA from 2002 to 2016. Patients with COPD were compared to patients without COPD applying multivariable Cox regression models and propensity-score matching for evaluation of the primary prognostic endpoint defined as long-term all-cause mortality at 2 years. Secondary endpoints were all-cause mortality at index, at 30 days and after discharge, cardiac death at 24 h, rehospitalization related to cardiac causes and the composite endpoint of cardiac death at 24 h, recurrences of ventricular tachyarrhythmias and appropriate ICD therapies at 2 years. Results: In 2813 unmatched high-risk patients with ventricular tachyarrhythmias and SCA, COPD was present in 9%. VF was less common in COPD (28% versus 39%; p = 0.001). Multivariable Cox regression models revealed that COPD was associated with the primary endpoint of long-term all-cause mortality (HR = 1.245; 95% CI 1.001–1.549; p = 0.001), which was also proven after propensity score matching (log rank p = 0.001). The secondary endpoints of all-cause mortality at index, at 30 days, after discharge, cardiac death at 24 h, as well as the composite endpoint of cardiac death at 24 h, recurrences of ventricular tachyarrhythmias and appropriate ICD therapies were higher in COPD (p < 0.033). Conclusion: In high-risk patients presenting with ventricular tachyarrhythmias and SCA, COPD was associated with higher long-term all-cause mortality, cardiac death at 24 h and higher rates of the composite endpoint of cardiac death at 24 h, recurrences of ventricular tachyarrhythmias and appropriate ICD therapies at 2 years. Highlights: COPD increases mortality in patients with ventricular tachyarrhythmias and SCA. COPD was associated with the primary endpoint of long-term all-cause mortality. Results showed consistency in multivariable regression and propensity score matching. COPD was associated with secondary endpoints such as cardiac death at 24 h.